sys.begin to sys.exit. - Jucan, Ioana B. (TDR: The Drama Review (MIT Press))
What happens to theatre in an algorithmically driven world, and what becomes possible when algorithms and the software they constitute are put to work to make theatre? A Piece of Work by Annie Dorsen considers this question an exigent problem to be solved—algorithmically and theatrically.